Semantic Segmentation of Eye Fundus Images Using Convolutional Neural Networks - Toliušis, Ričardas; Kurasova, Olga; Bernatavičienė, Jolita (Information & Media, 2019)
This article reviews the problems of eye bottom fundus analysis and semantic segmentation algorithms used to distinguish the eye vessels and the optical disk. Various diseases, such as glaucoma, hypertension, diabetic retinopathy, macular degeneration, etc., can be diagnosed through changes and anomalies of the vesssels and optical disk. Convolutional neural networks, especially the U-Net architecture, are well-suited for semantic segmentation. A number of U-Net modifications have been recently developed that deliver excellent performance results.